Beyond the Developmental State
XIII, 182 p.
Keywords: This collection of essays examines the historical influence of states in East Asia's political economies, and considers their contributions to the ongoing social, economic and political transformation of the countries in this region. They show that the status of these so-called developmental states have evolved over time, and that their role and capacity have been significantly related to the social bases and cultural roots of the relevant countries.